Comparison between rupture/growth risk scores and treatment recommendation scores application to aneurysmal subarachnoid hemorrhage patients: A multicenter cross-reliability assessment study. (May 2022) - Stumpo, Vittorio; Latour, Kristy; Trevisi, Gianluca; Valente, Iacopo; D'Arrigo, Sonia; Olivi, Alessandro; Sturiale, Carmelo Lucio
Highlights: Two score systems may drive the aneurysms management: one estimates the growth/rupture risk, the other provides recommendation to treat. There is still a poor validation about the reliability of these score families and little is known about their agreement. When retrospectively applied, JTS outperforms UIATS in correctly recommending treatment in a higher percentage of SAH patients. UIATS and JTS agrees more with UCAS than PHASES predictions. Around 50% of patients with unclear or conservative UIATS/JTS recommendations are classified as at higher growth risk by ELAPSS and JGS. Abstract: Background: Two score families were introduced to help clinicians about the decision-making regarding intracranial aneurysms management. The first family estimates the growth/rupture risk (GRS), whereas the second provides straightforward recommendation (RS) for treatment decisions. However, both remain poorly validated and little is known about their agreement. In this paper, we performed a retrospective concordance analysis among the two scores families through their application to a multicenter cohort of SAH patients. Methods: Demographical, clinical and radiological data were extracted in conformance with the variables included in PHASES, UCAS, ELAPSS, Juvela's growth score (JGS), UIATS and Juvela's treatment score (JTS). Individual patients' score were calculated for both score families, and pooled data were then analyzed. Results: Overall, 146 patients were included. True positive rates were: 51.4% for PHASES; 71.9% for UCAS; between 60.3% and 90.4% for JTS; and between 27.4% and 68.5% for UIATS. In patients showing UIATS unclear recommendation and low JTS score (RS), UCAS outperformed PHASES (GRS) in identifying aneurysms at higher risk of rupture. Same results we found for patients with conservative UIATS recommendation and very low JTS score. Forty-to-sixty percent of aneurysms with unclear or conservative RS recommendation would have been identified as at high risk with GRS. Conclusions: Retrospectively applied, JTS appeared outperforming UIATS in correctly recommending treatment in a higher percentage of patients. UIATS and JTS appeared agreeing more with UCAS than PHASES predictions. Around 50% of patients with unclear or conservative UIATS/JTS recommendations were been classified as at higher growth risk by ELAPSS and JGS.